PERSPEKTIF BARU DALAM MANAJEMEN PENDIDIKAN: MENANGANI ISU KONTEMPORER DENGAN PENDEKATAN MULTIDISIPLINER - Puspita Rini, Puput; Dahila, Ida; Suherman, Suherman; Sholih, Sholih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article explores the application of a multidisciplinary approach in educational management to address contemporary issues modern educational institutions face. In the face of challenges such as globalization, rapidly changing technologies, and the need for inclusion and sustainability, traditional education systems often face pressure to adapt and be innovative. This article reviews a wide range of literature showing how a multidisciplinary approach facilitates a more holistic and comprehensive response to these challenges and encourages the development of a more dynamic and relevant curriculum that reflects real-world needs. Through a systematic analysis of previous studies, this article identifies that integrating disciplines such as information technology, psychology, and management can result in more effective educational strategies. Results from this review suggest that a multidisciplinary approach improves student engagement, learning satisfaction, and more adaptive policy development. Although challenges in its implementation cannot be ignored, primarily related to institutional restructuring and policy development, this article emphasizes the transformational potential of multidisciplinary approaches. This article suggests concrete strategies for engaging various stakeholders in education, provides policy recommendations and discusses practical implications for improving interdisciplinary collaboration. The implications of this research are essential for policymakers, educational administrators, and educators who seek to meet the demands of contemporary education and prepare students for future challenges.